Translation and validation of the Arabic version of the Chronic Illness Anticipated Stigma Scale in Saudi patients with multiple sclerosis - Alhujaili, Naseem A.; Alsulami, Salhah S. (Frontiers in Psychiatry, 2025)
BackgroundAnticipated stigma is associated with experiences of enacted stigma or discrimination from others in the past or the present based on one’s chronic illness. People diagnosed with chronic diseases report experiencing significant stigma from others, including social rejection from friends and family members, work termination from employers, and poor care from healthcare providers. The aim of this paper was to explain the translation procedure and the psychometric evaluation of the Arabic language version of the Chronic Illness Anticipated Stigma Scale (CIASS), which was designed and evaluated psychometrically in different countries and languages.MethodsThe Arabic version of the CIASS was given to 222 patients with multiple sclerosis (MS). Cronbach’s alpha was used to assess the internal consistency of the measured questionnaire. Structural equation modeling with confirmatory factor analysis using the maximum likelihood method was applied to evaluate the CIASS questionnaire in order to assess its factorial structure and validity for patients suffering from MS.ResultsThe Arabic version of CIASS is shown to have high reliability (Cronbach’s α = 0.89) and structural validity.ConclusionThe Arabic version of CIASS is a valid and reliable tool for the assessment of anticipated stigma among patients with MS. The use of this tool in the clinical setting can help to identify the source of stigma and guide its management accordingly. However, further validation studies among patients with different chronic illnesses are required.